PYROLYSIS OF HOLM OAK AND OLIVE WOOD - Figueiredo, J L (International Conference on Biomass for Energy and Industry, 1989)
The pyrolysis of olive and holm-oak wood to produce charcoal and fuel gas was studied in the temperature range from 3 00 to 9 00°C. The charcoals were characterized by proximate and ultimate analyses, and the gases were analyzed chromatographycally The fised carbon content of the charcoal increased with temperature up to 600-700°C and then remained essentially constant. The gases produced were mainly CO, CO , H and CH . The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is 600'C.
APS
Keywords: charcoal production; fuel gas; Holm oak; olive; pyrolysis